ANALISIS PEMASARAN USAHATANI TOMAT KELURAHAN BOYAOGE KECAMATAN TATANGA KOTA PALU - Elisa Elisa; Hadayani Hadayani; Effendy Effendy (Universitas Tadulako, 2016)
High tomatoes production in Boyaoge not necessarily has positive impact on farmers’ incomedue to the fluctuation of the tomatoes price. The aims of this study were to (1) identify the form of marketing channels and margins at each marketing channel in Boyaoge village Tatanga sub district of Palu City, (2) to determine tomatoes price in each marketing channel accepted by farmers in Boyaoge village Tatanga sub district of Palu City and (3) the determine marketing efficiency in each marketing channel in in Boyaoge village Tatanga sub district of Palu City. Farmer respondents 30 people were chosen using census method while traders using tracing sampling technique. The research results showed that the sale price of the tomatoes by the farmers in Boyaoge village Tatanga sub district of Palu City is either IDR 91,520,000/15 ha equal to IDR 60,800,000/ha. The tomato farming system in in Boyaoge village Tatanga sub district of Palu City is feasible to be developed as sshown by its two marketing channels: (1) Farmers à Collecting Traders à Distributing Traders à Consumers; (2) Farmers à Distributing Trader à Consumers. The total margin for each marketing channel was IDR 2,000/kg. The part of the price received by the farmers was 50% from either channel 1 or 2. The marketing channel 2 is more efficient than the marketing channel 2 as the ratio of the total cost to the sale price in the former marketing was 17.66% whereas the latter was 5.95%. KeyWords: Marketing, and Tomatoes Farming